Evaluating user-generated content in social media: an effective approach to encourage greater pro-environmental behavior in tourism? - Han, Wei; McCabe, Scott; Wang, Yi; Chong, Alain Yee Loong (Taylor & Francis, 2017)
Appealing to tourists’ intrinsic interest for high-quality tourism environments, and thus encouraging them to act with a greater sense of personal responsibility toward the environment, could be critical to promoting sustainable tourism. Proliferating media channels makes the choice, style and delivery of pro-environmental messages a key issue for tourism marketers and management. Social media has become a recognized important channel for tourism information, with user-generated content (UGC) being more trusted than official channels, yet there is little knowledge about its potential role in activating pro-environmental norms. This study investigates that issue. Focusing on the conjoining aspects of personal and social norms for the first time, we propose a hypothetical model to explain the direct and indirect effects of pro-environmental UGC in activating tourists’ pro-environmental behavioral intentions. Working in a Chinese context, where social media plays an increasing role, the research, using a web-based sample (N = 1043), UGC-linked pro-environmental knowledge and awareness, was found to have a strong role in activating pro-environmental norms, creating a pro-environment online community, and increasing tourists’ level of engagement in pro-environmental social media activity. The study highlights the effectiveness of social media channels with UGC providing persuasive communications able to impact sustainable behaviors.